A global inventory of concentration measurements of free and dissolved in underground waters molecular hydrogen in the Earth’s crust on land - O.M. Rusakov (Геофизический журнал, 2020)
This paper presents a global inventory of concentration measurements of free and dissolved in underground water molecular hydrogen sampling areas in the Earth’s crust on land. The inventory table indicates their regional belonging, the average hydrogen concentration and standard deviation at each point if concentration exceeds 0.01 %. For information analysis, sampling reservoirs are classified in 5 groups depending on the type of degassing structures. They are ophiolite complexes, geothermal systems, underground waters, ultrabasite massifs, and soils. Samples were taken on 5 continents in 32 countries from 97 reservoirs in 318 sampling areas. The 3481 gas analyzes revealed the presence of hydrogen of different concentrations. The 294 values of R/Ra were presented. All sampling reservoirs are plotted on a world map, which also shows the position of wells in the territory of the former USSR, where hydrogen from underground waters was recorded. In general, most of the reservoirs studied contain hydrogen in small quantities, since on-ly 16 (16.5%) of them have concentration of more than 5 %. The highest concentration of hydrogen (average value of 60.34 %, 7 wells) is in the heads of hydrogeological wells immediately after drilling completion. The concentration of hydrogen in soil near wells is 1070—1600 times less than hydrogen in the wells coming from underground water horizons. Zones of the present-day activation accompanied with intensive geothermal processes generate low concentration hydrogen, whose mean concentration value is 1.6 ± 3.97 % (43 analyses). In soil gases, the hydrogen concentration varies from 0.03 to 0.06% with exception of the Moscow region (0.25 %). The concentration of hydrogen in soil of the zones of active faults varies randomly along the faults depending on the composition of the sedimentary rocks filling them. Only in the zones of active faults during several years of preparation of strong earthquakes in the region hydrogen released to the day surface whose concentration exceeds the background value by 200 times reaching 4 %. The presence of hydrogen in gases with the mantle component was mentioned 14 times in publications mainly due to the values of R/Ra. However, the first integrated study of helium isotopes relationships and seismotomographic data suggests a unique case of occurrence of mantle hydrogen in one of geothermal features of the Yellowstone caldera. The present-day water plays a key role in the formation of hydrogen. Its generation occurs exclusively in the Earth’s crust because of the oxidation of ferrous iron by alkaline water in basic and ultrabasic rocks resulted from various chemical reaction schemes and water vapor always occurrence in magmatic gases where hydrogen is registered 24 times. In rare cases (4), the source of hydrogen in negligible quantities is alkaline water radiolysis or radioactive decay.